Role of interventional radiology in surgical diseases of breast - Mohammad Sohail Asghar,; Asgher, Mohammad Zohaib; Abdul Wahab,; Aslam, Jaweria; Zafarullah, Sadaf (Journal of the Pakistan Medical Association, 2023)
Since the publication of the first imaging-guided wire localisation technique, the art of breast treatments has made great strides. Radiologists like Hall, Frank, Kopans, DeLuca, and Homer were all the pioneers in innovative breast interventional radiology field. Their approaches and gadgets for enhancing surgical outcomes in cases with breast diseases aided progress in the discipline and have withstood the ravages of time. Many of their methods are still in use. We are all standing together at the beginning of a new chapter in medicine. Cost effectiveness, comparative effectiveness studies, and an older population are all causing clinicians to reconsider what they perform. Similarly, we are now united on a global scale. The studies described in the current narrative review relate to multiple nations around the world. Breast cancer is a worldwide health problem. ---Continue